2018
DOI: 10.1016/j.theriogenology.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dairy cow inter-service interval and probability of conception

Abstract: Recent research has indicated that the interval between inseminations in modern dairy cattle is often longer than the commonly accepted cycle length of 18-24 days. This study analysed 257,396 inseminations in 75,745 cows from 312 herds in England and Wales. The interval between subsequent inseminations in the same cow in the same lactation (inter-service interval, ISI) were calculated and inseminations categorised as successful or unsuccessful depending on whether there was a corresponding calving event. Conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
3
8
0
1
Order By: Relevance
“…A trend was present for services following even longer intervals (25 to 31 d) to have greater predicted probability of pregnancy than quartile 1. This corresponds with recent observations by Remnant et al (2018) that services after intervals of 25 and 26 d were significantly more likely to result in pregnancy than services following intervals of 17 and 18 d. These findings suggest that some of the mechanisms underlying extended intervals might have a positive effect on fertility. This could support the hypothesis that longer intervals are due to 3-wave cycles as some (although not all) studies have demonstrated higher pregnancy rates for 3-wave cycles (Ahmad et al, 1997;Townson et al, 2002;Bleach et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A trend was present for services following even longer intervals (25 to 31 d) to have greater predicted probability of pregnancy than quartile 1. This corresponds with recent observations by Remnant et al (2018) that services after intervals of 25 and 26 d were significantly more likely to result in pregnancy than services following intervals of 17 and 18 d. These findings suggest that some of the mechanisms underlying extended intervals might have a positive effect on fertility. This could support the hypothesis that longer intervals are due to 3-wave cycles as some (although not all) studies have demonstrated higher pregnancy rates for 3-wave cycles (Ahmad et al, 1997;Townson et al, 2002;Bleach et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…If estrous cycle length has changed, these measures may give false impressions of herd performance. Additionally, although some researchers have demonstrated that interestrus intervals outside of a range of 18 to 24 d have a negative association with insemination success, more recent studies have contradicted this, showing improved pregnancy outcomes to insemination following longer interestrus intervals (Royal et al, 2000;Remnant et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…e observed interservice interval of 18-24 days for more than two-thirds of repeat breeding heifers and multiparous animals at the population level indicated a very good oestrus detection. Remnant et al (2018) reported that interservice interval of 19-26 days indicated that this period is the true latent distribution for the interservice interval with the optimal reproductive outcome, suggesting day-22 with the increased probability of conception [25]. However, we found that a total of 9.6% of interservice intervals were longer than 48 days ( Figure 6).…”
Section: Discussionmentioning
confidence: 65%
“…Inseminations performed at intervals of 18 to 24 or 36 to 48 days are considered normal or indicative of a missed heat, respectively, while intervals outside of these ranges are abnormal. More recent research has suggested that normal interservice intervals may be more variable, and a range of 18 to 28 days may be more accurate (Remnant and others 2018).…”
Section: Key Drivers Of Reproductive Performancementioning
confidence: 99%